2022
DOI: 10.26434/chemrxiv-2022-69tc7-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nickel-Catalyzed Electrochemical Reductive Cross-Electrophile Coupling of Alkylpyridinium Salts and Aryl Halides

Abstract: An electrochemically driven, nickel-catalyzed cross-electrophile coupling reaction of alkylpyridinium salts and aryl halides is reported. High-throughput experimentation (HTE) was employed for rapid reaction optimization and evaluation of a broad scope of pharmaceu-tically relevant structurally diverse aryl halides, including complex drug-like substrates. In addition, the transformation is compatible with both primary and secondary alkylpyridinium salts. Systematic comparisons of the electrochemical and non-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Producing carbon–carbon bonds from readily available feedstocks is particularly impactful. The C­(sp 3 )–C­(sp 2 ) substructure is often synthesized from an organometallic reagent and an alkyl or aryl (pseudo)­halide via cross-coupling with palladium, nickel, copper, iron, cobalt, or other metal catalysts. Recently, nickel catalysis has found complementary utility in reductive C­(sp 3 )–C­(sp 2 ) couplings. …”
mentioning
confidence: 99%
“…Producing carbon–carbon bonds from readily available feedstocks is particularly impactful. The C­(sp 3 )–C­(sp 2 ) substructure is often synthesized from an organometallic reagent and an alkyl or aryl (pseudo)­halide via cross-coupling with palladium, nickel, copper, iron, cobalt, or other metal catalysts. Recently, nickel catalysis has found complementary utility in reductive C­(sp 3 )–C­(sp 2 ) couplings. …”
mentioning
confidence: 99%
“…While arylation of N-alkylpyridiniums is well-known for bromoarenes, effective coupling of chloroarenes remains undeveloped. 18 We hypothesized that, in addition to avoiding the aryl homodimer, the increased electron density of L5 may allow for more rapid oxidative addition into chloroarenes. We found that the equivalent chloroarene coupled in 55% yield using the same conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Methods from Weix, 15−17 Sevov, 18 and others 12 , 19−21 have demonstrated the use of multimetallic catalyst systems, where one catalyst is exclusively responsible for generation of an alkyl radical, and another engages the C(sp 2 ) coupling partner and facilitates formation of the desired C−C bond (Figure 1C, part i). 22,23 An alternative approach is the addition of stoichiometric additives�such as phthalimide or pyridine deriva-tives�that passivate open sites of the arylnickel intermediate, slowing the rate of deleterious disproportionation (Figure 1C, part ii).…”
Section: ■ Introductionmentioning
confidence: 99%
“…47 One important aspect of our method, which is unprecedented in the field of homolytic Ca-N cleavage, is that it would provide a general way to interconvert an alkyl primary amine into pyridine derivatives, in substrates with a Ca-primary, secondary or tertiary carbon. This approach complements the use of pyridinium salts 48 in transition metal-catalyzed cross-coupling reactions to prepare functionalized pyridines (limited to Ca-primary and Casecondary) [49][50][51][52][53][54] or the use of ammonium salts in photoinduced processes, limited to the use of benzylic substrates. 55,56…”
Section: Introductionmentioning
confidence: 99%